Development of a Self-Emulsifying Drug Delivery System for Optimized Topical Delivery of Clofazimine - Daniélle van Staden; Jeanetta du Plessis; Joe Viljoen (MDPI AG, 2020)
A quality-by-design and characterization approach was followed to ensure development of self-emulsifying drug delivery systems (SEDDSs) destined for topical delivery of the highly lipophilic clofazimine. Solubility and water-titration experiments identified spontaneous emulsification capacity of different excipient combinations and clofazimine. After identifying self-emulsification regions, check-point formulations were selected within the self-emulsification region by considering characteristics required to achieve optimized topical drug delivery. Check-point formulations, able to withstand phase separation after 24 h at an ambient temperature, were subjected to characterization studies. Experiments involved droplet size evaluation; size distribution; zeta-potential; self-emulsification time and efficacy; viscosity and pH measurement; cloud point assessment; and thermodynamic stability studies. SEDDSs with favorable properties, i.e., topical drug delivery, were subjected to dermal diffusion studies. Successful in vitro topical clofazimine delivery was observed. Olive oil facilitated the highest topical delivery of clofazimine probably due to increased oleic acid levels that enhanced stratum corneum lipid disruption, followed by improved dermal clofazimine delivery. Finally, isothermal microcalometric experiments studied the compatibility of excipients. Potential interactions were depicted between argan oil and clofazimine as well as between Span®60 and argan-, macadamia- and olive oil, respectively. However, despite some mundane incompatibilities, successful development of topical SEDDSs achieved enhanced topical clofazimine delivery.